Pigmented Villonodular Synovitis of the Ankle and Subtalar Joint Treated by Surgical Excision and Ligament Reconstructions: A Case Report - Shin, Jae-Hyuk; Lee, Byung Hoon; Kim, Gab-Lae; Kim, Kwon (Journal of Korean Foot and Ankle Society, 2016)
Diffuse pigmented villonodular synovitis (PVNS) involving ankle joint needs complete mass excision and total synovectomy to reduce recurrence rate, while surrounding ligaments can be easily damaged. So the concurrent ligament reconstruction should be considered for post-excisional instability in subtalar joint as well as lateral ankle joint. We describe our experience in the management of a diffuse type PVNS, invades lateral talocrural joint extended to subtalar joint and introduce a new technique of all-in-one reconstruction for anterior talofibular,calcaneofibular and cervical ligament. Our new reconstruction technique applying modified Chrisman and Snook technique is useful in stabilization for deficiencies of the ligament complexafter PVNS excisionat lateral ankle and subtalar joint. KCI Citation Count: 0